Priority Setting for Improvement of Cervical Cancer Prevention in Iran - Azam Majidi; Reza Ghiasvand; Maryam Hadji; Azin Nahvijou; Azam-Sadat Mousavi; Minoo Pakgohar; Nahid Khodakarami; Mehrandokht Abedini; Farnaz Amouzegar Hashemi; Marjan Rahnamaye Farzami; Reza Shahsiah; Sima Sajedinejhad; et al. (Kerman University of Medical Sciences, 2016)
Background Cervical cancer is the fourth most common cancer among women worldwide. Organized cervical screening and vaccination against human papilloma virus (HPV) have been successful interventions for prevention of invasive cervical cancer (ICC). Because of cultural and religious considerations, ICC has low incidence in Iran and many other Muslim countries. There is no organized cervical screening in these countries. Therefore, ICC is usually diagnosed in advanced stages with poor prognosis in these countries. We performed a priority setting exercise and suggested priorities for prevention of ICC in this setting. Methods We invited experts and researchers to a workshop and asked them to list important suggestions for ICC prevention in Iran. After merging similar items and removing the duplicates, we asked the experts to rank the list of suggested items. We used a strategy grid and Go-zone analysis to determine final list of priorities for ICC prevention in Iran. Results From 26 final items suggested as priorities for prevention of ICC, the most important priorities were developing national guidelines for cervical screening and quality control protocol for patient follow-up and management of precancerous lesions. In addition, we emphasized considering insurance coverage for cervical screening, public awareness, and research priorities, and establishment of a cervical screening registry. Conclusion A comprehensive approach and implementation of organized cervical screening program is necessary for prevention of ICC in Iran and other low incidence Muslim countries. Because of high cost for vaccination and low incidence of cervical cancer, we do not recommend HPV vaccination for the time being in Iran.